Investigation of Heat and Mass Transfer in the Process of Fuel Preparation from Biomass Particles with High Moisture - A. V. Mitrofanov; O. B. Kolibaba; R. N. Gabitov; D. A. Dolinin; S. V. Vasilevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Currently, in a number of countries an urgent task for development of fuel and energy complexes is to increase the share of generation by involving solid fuels in circulation. Among such projects, those that allow the disposal of waste from various industries are particularly significant. Expired food products in this context are represented as a renewable local energy resource. However, such products require serious activities to prepare them for incineration or other type of high-temperature processing in order to obtain energy. The purpose of the present work is to improve methods of preparing fuel from recycled carrot fruits (unsuitable for use in the food sector). During the fuel preparation of carrots, the drying stage is limiting for the rational organization of its processing in boilers. In addition, the drying stage is extremely energy-consuming, so reliable prediction of its kinetics largely determines the efficiency of the entire technological process. In the course of the study, the following tasks were solved: a numerical method was developed for describing the processes of internal and external heat and mass transfer problems using an explicit difference approximation of differential equations of heat and mass transfer; parametric identification of the proposed one-dimensional mathematical model was performed using empirical dependencies known from literature sources; empirical verification of the proposed mathematical model was carried out by comparing the calculated forecasts obtained with the results of their own field experiments. The fact that the proposed mathematical model and the results of the full-scale experiment are independent, while the calculated forecasts and experimental data are in good agreement, makes us possible to consider the proposed calculation method as a reliable scientific basis for a computer method for calculating of heat and mass transfer processes when organizing the preparation of fuel from carrot fruits.